Acute symptomatic seizures and epilepsy after mechanical thrombectomy. A prospective long-term follow-up study. (July 2021) - Alemany, M; Nuñez, A; Falip, M; Lara, B; Paipa, A; Quesada, H; Mora, P; De Miquel, MA; Barranco, R; Pedro, J; Cardona, P
HIGHLIGHTS: In our cohort of 344 consecutive patients with acute ischaemic stroke, thrombectomy did not increase the risk of ASS (acute symptomatic seizures) or poststroke epilepsy (PSE). 2) ASS is a risk factor for suffering PSE. 3) Having suffered ASS and/or PSE does not increase acute mortality or 5-year mortality. 4) A higher percentage of reperfusion is independently associated with an increased risk of ASS. Abstract: Introduction: New treatments for acute ischaemic stroke, such as mechanical thrombectomy, can achieve reperfusion of large ischaemic tissue. Some studies have suggested that reperfusion therapies can increase the risk of suffering acute symptomatic seizure (ASS) and poststroke epilepsy (PSE). The aim of the study was to determine the incidence of ASS and PSE in patients undergoing thrombectomy, and related factors. Patients and methods: This was a retrospective single-centre study including patients with ischaemic stroke and NIHSS> 8 treated with thrombectomy with a follow-up ≥5 years. We evaluated several epidemiological, radiological, clinical and electroencephalographic variables. Results: Of the 344 included patients, 21 (6.1%) presented ASS, 53 (15.40%) died in the acute phase, and 13 (4.46%) died during the first year. The degree of reperfusion (p 0.029), advanced age (p 0.035), and haemorrhagic transformation (p 0.038) increased the risk of suffering ASS, with degree of reperfusion being an independent factor, OR 2.02 (1.21-4.64). The incidence of PSE was 4.12% in the first year, 3.72% in the second, and 1.61% in the fifth. The accumulated incidence at 5 years was 8.93%. Related risk factor for suffering PSE was ASS (p < 0.001), yielding an OR value of 2.00 (1.28-3.145). Conclusions: Thrombectomy doesn´t increase the risk of ASS. A higher percentage of reperfusion, advanced age, and haemorrhagic transformation are associated with an increased risk of ASS. ASS is a risk factor for suffering PSE. In terms of mortality, having suffered ASS and/or PSE does not increase acute or long-term mortality.